1998
DOI: 10.1152/jappl.1998.84.3.902
|View full text |Cite
|
Sign up to set email alerts
|

Time course of changes in capillarization in hypertrophied rat plantaris muscle

Abstract: The time course of angiogenesis during hypertrophy of the rat plantaris muscle was studied by using a unilateral, synergistic ablation model. Animals (n = 6/group) were euthanized 2, 5, 7, 15, 21, and 30 days postmyectomy. Sections from both the hypertrophied and contralateral muscles were simultaneously stained for capillaries and muscle fiber type. Mean fiber cross-sectional area (FA) and various indexes of capillarity were determined by using a video analysis system. The capillary supply to individual fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 33 publications
11
57
1
Order By: Relevance
“…It is striking, however, that the local capillary supply was more tightly related to FCSA than fibre oxidative capacity. Consistent with these observations, fibre hypertrophy and angiogenesis during muscle overload have a similar time course (Plyley et al, 1998), further supporting a coupling between fibre size and local muscle capillarisation. Such a coupling is, in part, explicable by the fact that not only muscle fibres and satellite cells, but also endothelial cells act as mechanotransducers and may secrete factors with reciprocal effects in response to mechanical deformation (Christov et al, 2007).…”
Section: Resultssupporting
confidence: 79%
“…It is striking, however, that the local capillary supply was more tightly related to FCSA than fibre oxidative capacity. Consistent with these observations, fibre hypertrophy and angiogenesis during muscle overload have a similar time course (Plyley et al, 1998), further supporting a coupling between fibre size and local muscle capillarisation. Such a coupling is, in part, explicable by the fact that not only muscle fibres and satellite cells, but also endothelial cells act as mechanotransducers and may secrete factors with reciprocal effects in response to mechanical deformation (Christov et al, 2007).…”
Section: Resultssupporting
confidence: 79%
“…Since plantaris overload causes both an increased muscle mass as well as increased Type I MHC expression (Noble et al 1983, Locke et al 1994, Plyley et al 1998, Macpherson et al 1999, it was necessary to consider changes in Type I MHC in context to changes in muscle mass. After 1 day of overload, plantaris muscle Type I MHC content remained unchanged from their respective contralateral controls, regardless of whether animals experienced a prior heat stress (no significant differences were observed).…”
Section: Type I Mhc Contentmentioning
confidence: 99%
“…It is well known that increased muscle fiber size and increased protein content occur following overload (Hubbard et al 1975, Plyley et al 1998, Macpherson et al 1999. During the process of muscle hypertrophy, muscle fibers adapt by increasing the number of sarcomeres, mostly in parallel (peripheral accumulation of sarcomeres) and, to a much lesser extent, in series (elongation of existing fibers).…”
Section: Type I Mhc Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, myofiber atrophy that occurs with aging, disuse, and myopathic disease is associated with capillary loss (8,28). It has been shown that angiogenesis and compensatory muscle hypertrophy are temporally coupled, suggesting that these two processes may be controlled by common regulatory mechanisms (47). However, nothing is known about the molecular events that coordinate myofiber hypertrophy and the recruitment of new blood vessels.…”
mentioning
confidence: 99%